Keteladanan Ustadzah dalam Meningkatkan Kedisiplinan Shalat Berjamaah Santri Putri di Pondok Pesantren Hidayatul Mubtadiin Jati Agung Lampung Selatan Tahun Ajaran 2024/2025 - Damayanti, Desi; Eko Wati, Endang; Anita, Anita (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This obligation was not given arbitrarily, but rather through a significant event known as Isra’ Mi’raj. The purpose of this study is to reveal how female religious teachers (ustadzah) play a role in motivating female students (santri putri) to improve their discipline in performing congregational prayers (salat berjamaah), how they build awareness of the importance of congregational prayer, and how they implement habitual training to instill greater discipline in performing it at the Hidayatul Mubtadiin Islamic Boarding School (Pondok Pesantren). This research uses a qualitative descriptive approach with a case study method. Data collection techniques include direct observation, interviews, and documentation. The research location is at the Hidayatul Mubtadiin Islamic Boarding School, with informants including the head of the boarding school, administrators in charge of religious affairs (jam’iyah), other boarding school staff, and the female students. The results show that ustadzah play a crucial role in developing the discipline of congregational prayer among female students. This role is realized through good personal example, personal engagement, and continuous guidance. In instilling awareness, the ustadzah begin by internalizing spiritual values and explaining the meaning and purpose of prayer as a direct connection between servant and Allah SWT. In addition, the ustadzah encourage regular congregational prayer habits, such as waking students 15 minutes before the call to prayer (adhan), creating a religious environment in the boarding school, and reinforcing habits through consistent example and discipline. The success of the ustadzah in fostering prayer discipline among female students is also supported by the firmness of the school administrators in enforcing the rules, including giving direct examples and applying timely sanctions to students who fail to attend congregational prayer